Kajian yuridis tentang merek terkenal dan upaya hukum terhadap pelanggarannya - Kevien Dicky Aldison; Sunarjo Sunarjo; Hendra Djaja (University of Merdeka Malang, 2021)
International trademark regulation is based on the Paris Convention and The Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) while in Indonesia the regulation regarding trademark has undergone several changes, most recently Law Number 20 of 2016 concerning Trademarks and Geographical Indication. A trademark can be said to be a well-known trademark if it meets the criteria for a well-known trademark, but the latest Indonesia trademark law does not clearly explain the criteria for it. This study uses a normative juridical approach. This approach focuses on examining literature materials such as legislation and other relevant sources. This study examines the criteria for a well-known trademark by making comparisons between existing laws in Indonesia and countries and examines what legal remedies can be taken if a violation occurs. The results of this study indicate that there are several criteria for a well-known trademark that can be applied in Indonesia from the regulations of other countries to provide legal certainty. Some of these criteria are records of successful use of marks, trademarks that have been registered in various countries and those that are not yet in the Indonesian legal system, namely special registration of a well-known trademark. For legal measures against infringement of the well-known trademark, it can be done in court (litigation) or outside the court (non-litigation) such as dispute resolution through arbitration.How to cite item: Aldison, K. D. Sunarjo., Djaja, Hendra. (2021). Kajian yuridis tentang merek terkenal dan upaya hukum terhadap pelanggarannya. Jurnal Cakrawala Hukum, 12(1), 41-50.doi:10.26905/idjch.v12i1.5723.